Biaxially strained germanium crossbeam with a high-quality optical cavity for on-chip laser applications - Jung, Yongduck (2021)
The creation of CMOS compatible light sources is an important step for the realization of electronic-photonic integrated circuits. An efficient CMOS-compatible light source is considered the final missing component towards achieving this goal. In this work, we present a novel crossbeam structure with an embedded optical cavity that allows both a relatively high and fairly uniform biaxial strain of ~0.9% in addition to a high-quality factor of >4,000 simultaneously. The induced biaxial strain in the crossbeam structure can be conveniently tuned by varying geometrical factors that can be defined by conventional lithography. Comprehensive photoluminescence measurements and analyses confirmed that optical gain can be significantly improved via the combined effect of low temperature and high strain, which is supported by a three-fold reduction of the full width at half maximum of a cavity resonance at ~1,940 nm. Our demonstration opens up the possibility of further improving the performance of germanium lasers by harnessing geometrically amplified biaxial strain.